A facile emulsion-combustion processing of IR reflective, antibacterial and antifungal ceria for surface engineered functional textiles. Issue 19 (1st October 2022) - Sri Bala Jeya Krishna Sri, P.; Muthusundar, K.; Peer Mohammed, A.; Ananthakumar, S.
Abstract: Emulsion-combustion reaction was performed using cerous carbonate-urea emulsion prepared in hexane/water medium by mechanical milling with CTAB surfactant. Prolonged exposure of the urea-cerous carbonate emulsion mixture at 90 °C, undergoes slow and steady flameless, 'smouldering' that caused localized micro-thermal heating. Ultimately simultaneous decomposition of cerous carbonate and urea occurred, finally produced crystalline, soft ceria agglomerates consisting of fluorite CeO2 particles. Ceria thus obtained was studied for the optical reflectance in the wavelength 700–2400 nm to understand the total solar reflectance quality [TSR]. The product was also systematically characterized for phase purity, morphology, UV absorbance, band gap as well as surface chemistry using XPS analysis. The Near IR reflectance data confirms 94% reflectance in the IR region. Antibacterial and antifungal studies were conducted against Escherichia coli, Staphylococcus aureus, Klebsiella, Candida albicans, and Aspergillus Niger . Subsequently, this IR reflective, antimicrobial ceria was dispersed in an acrylic-sodium silicate hybrid dispersant cum binder system for ceria spray coatings on fabrics used for making face masks. The IR reflectance and hydrophobic properties of ceria coated masks were examined. This study explored the beneficial properties of IR reflective, antimicrobial, hydrophobic CeO2 for the processing of surface engineered, multifunctional textiles for the medical sector. Abstract : Nano ceria preparation from cerous carbonate via Emulsion-combustion route@90 °C and functionality of ceria modified fabrics were highlighted in this work. Image 1